Mystical Love in Confession X: An Inquiry on the Name of the Divine - Simeon Theojaya (Asosiasi Teolog Indonesia, 2013)
“God ” is, in the first place, a name. Before being a person or Being, the name “God” could be anything imaginable. “What’s in a name?” “Who is the one that we love and how could we finally give account to it?” Such are the questions this paper will try to answer. This study will conduct a reading based largely on Augustine’s Confessions X, and will be dissected into two smaller parts. In the first part, I will propose the possibility of applying a mystical approach to address this issue. Then I will examine how the saint travels across his memory in search of God, as a demonstration of the mystical journey into love.